Desempenho agronômico de híbridos de milho na região de Araras- SP - Fernandes, Victor Hugo (Universidade Federal de São Carlos, 2025)
Maize (Zea mays L.) is an essential food in the global diet and holds significant economic relevance. However, abiotic stresses have impacted the performance of established hybrids. In this context, the present study aimed to evaluate the agronomic performance of six commercial maize hybrids in the region of Araras–SP, Brazil. The experiment was conducted in a randomized complete block design (RCBD), with four replications, using the hybrids NK467 VIP3, NS505 VIP3, NS 71 VIP3, NS 75 VIP3, NS 44 TG, and AG8780 PR04. Phenological traits, plant population, morphophysiological characteristics, yield components, and productivity were evaluated. Male flowering varied between 48 and 55 days. For female flowering, a significant delay regarding male flowering (asynchrony) was observed in the most sensitive materials, compromising pollination, with negative emphasis on NS 75 VIP3. The final plant stand was lower for NS 505 VIP3 and NS 75 VIP3, while AG8780 PR04 achieved the highest stand. The hybrids NK467 VIP3, NS 71 VIP3, and NS 44 TG showed greater plant height. Among yield components, NS 44 TG stood out with the highest number of grains per row and the greatest 100-grain weight, resulting in high productivity (6,700 kg ha⁻¹) and demonstrating greater rusticity against thermal-water stress. The hybrid NS 75 VIP3 had the lowest performance, penalized by low stand and poor grain filling.
Agronomic performance of maize hybrids in the Araras-SP region
Keywords: Zea mays L.; Interação genótipo x ambiente; Graus-dia; Estresse abiótico; Genotype x environment interaction; Growing degree days; Abiotic stress; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; 2. Fome Zero e Agricultura Sustentável; 12. Consumo e Produção Responsáveis